Failure to repeatedly supercompensate muscle glycogen stores in highly trained men - McInerney, P.; Lessard, S. J.; Burke, L. M.; Coffey, V. G.; Lo Giudice, S. L.; Southgate, R. J.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2005)
Purpose: It is not known whether it is possible to repeatedly supercompensate muscle glycogen stores after exhaustive exercise bouts undertaken within several days.